PEMBENIHAN IKAN LELE DUMBO (Clarias gariepinus) di BALAI BENIH IKAN (BBI) KABAT, BANYUWANGI - Abdul Wafi; Setyoharini Setyoharini (Faculty of Science and Technology University Ibrahimy, 2013)
The research objective was to determine the fish hatchery techniques of African catfish ( Clarias gariepinus ) at Fish Seed Kabat village Pakistaji District of Banyuwangi. Activities carried out starting from the preparation of the parent , the parent maintenance , spawning , hatching eggs , eggs treatment , seed treatment , and harvesting the seed . Parent Dumbo Catfish ( Clarias gariepinus ) were used in this study has a weight of 1.5 kg , with a ratio of 1 : 1 ( one tail of the male and female parent ) . Feed the fish seed of African catfish ( Clarias gariepinus ) is provided in the form of natural feed silk worms , and artificial feed in the form of boiled egg yolk mixed with milk powder . In order to combat infectious diseases such as anti-biotic be giving super tetra capsule with a volume of 5 liters . Seed harvesting is done in two ways: partial harvesting and harvesting total ..